Antibacterial silicone adhesive and preparation method thereof
By using modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediates in silicone glue and adding antibacterial and anti-mold composite agents, the problem of insufficient anti-bacterial durability of silicone glue is solved, and its anti-mold effect and construction performance in humid environments are significantly improved.
Patent Information
- Application Number
- CN202510059004.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silicone glue is insufficient antibacterial durability in humid environments, resulting in bacteria and mold growing in building seals, affecting aesthetics and hygiene.
Modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediates are used as fillers, and antibacterial and anti-mold composite agent composed of β-cyclodextrin, octyl isothiazolinone and tetracorneal zinc oxide whiskers are added to optimize the raw material composition and preparation process of silicone glue.
It significantly improves the antibacterial durability and mildew resistance of silicone glue, enhances its acid and alkali resistance and corrosion resistance in humid environments, and improves rheological performance and construction convenience.
Smart Images

Figure BDA0005242675150000081 
Figure BDA0005242675150000091 
Figure BDA0005242675150000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of silicone adhesive materials, and in particular, relates to an antibacterial silicone adhesive and a preparation method thereof. Background Art
[0002] With the rapid development of the construction industry, silicone sealants for construction play an increasingly important role in building sealing. Silicone sealants are usually paste-like materials composed of basic rubber, fillers, curing and other additives. They have the characteristics of strong adhesion, good weather resistance, good vibration resistance, and adaptability to large changes in cold and heat. They are bonded to the building substrate and provide a certain bonding strength between the substrates. They can achieve adhesion between most building materials products and have wide applicability. However, when using silicone sealant materials, related problems are also encountered, the most important of which is mildew resistance. In some humid environments, such as toilets, washbasins, wall joints in the bathroom, cabinets, sinks in the kitchen, etc., bacteria, molds and other microorganisms are very easy to breed and multiply in large numbers at the joints, causing the silicone sealant to turn yellow and black, which has a certain impact on appearance and hygiene. Therefore, the study of mildew resistance of silicone materials is a difficult problem that needs to be overcome in this technical field.
[0003] Chinese patent CN103773308A discloses a long-lasting antibacterial and mildew-proof silicone adhesive and a preparation method thereof. The technical solution mainly utilizes a coupling agent to combine an organic mildew-proof agent and an inorganic mildew-proof agent together. The coupling agent in the technical solution is one of γ-(2,3-epoxypropoxy) (KH-560) propyltrimethoxysilane or γ-(methacryloyloxy) propyltrimethoxysilane (KH-570). KH560 is a colorless, transparent liquid that is easily soluble in a variety of organic solvents, easily hydrolyzed, and condensed to form polysiloxane. KH-570 is a methacryloxy-functional silane that is mainly used to treat glass fiber and is not suitable for long-term dark and humid environments.
[0004] Chinese patent CN113881393 A discloses a silicone adhesive with anti-mold effect, which has an inhibitory effect not only on conventional molds and bacteria, but also on methicillin-resistant Staphylococcus aureus (MRSA) by adding a new composite anti-mold agent composed of nano zinc oxide and camphor wood powder extract. However, although nano zinc oxide and camphor wood powder have good antibacterial effects, the material still has the defect of weak sustained antibacterial effect.
[0005] Therefore, in the field of silicone rubber material technology, research on the antibacterial durability of materials is still a direction that technical personnel in this field need to continue to tackle. Summary of the invention
[0006] In view of the problem that the existing silicone glue has insufficient antibacterial durability, the following technical solutions are provided:
[0007] The technical solution of the present invention is specifically as follows:
[0008] An antibacterial silicone adhesive comprises the following raw materials in parts by weight: 80-90 parts of a base adhesive, 10-20 parts of a filler, 10-20 parts of a plasticizer, 5-8 parts of a crosslinking agent, 3-5 parts of a coupling agent, 0.2-0.8 parts of a catalyst, and 1-2 parts of an antibacterial and mildewproof composite agent. The filler is a mixture of modified nano-calcium carbonate and a maleic anhydride grafted modified graphene intermediate.
[0009] Preferably, the mass ratio of the modified nano-calcium carbonate and the maleic anhydride grafted modified graphene intermediate mixture is 1:1-2.
[0010] Preferably, the antibacterial and antifungal composite agent is composed of β-cyclodextrin, octyl isothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:1-2:1.
[0011] Preferably, the base glue is α,ω-dihydroxy polydimethylsiloxane, the plasticizer is polydimethylsiloxane, the crosslinking agent is methyl triacetoxysilane, and the coupling agent is γ-
[0012] (2,3-epoxypropoxy)propyltrimethoxysilane, the catalyst is dibutyltin diacetate.
[0013] Preferably, the modified nano-calcium carbonate preparation method is as follows: at 60-80°C, 20-40% concentration of CO2 is introduced into lime emulsion, when the carbonization reaction is completed to generate calcium carbonate, CH3(CH2)10COONa is first added in an amount of 5-10% by weight of the calcium carbonate, stirred for 50-60 minutes, and CaCl2 is continuously added in an amount of 0.5-2.5% by weight of the calcium carbonate, stirred for 10-20 minutes, aged for 30-40 minutes, filtered, and dried at 60-90°C to obtain the modified nano-calcium carbonate.
[0014] Preferably, the preparation method of the maleic anhydride grafted modified graphene intermediate mixture is:
[0015] S1: By weight, take 10 parts of α,ω-dihydroxypolydimethylsiloxane, 12 parts of maleic anhydride, 3 parts of benzoyl peroxide, and 100 parts of graphene powder.
[0016] S2: heating a 10-20% mass concentration sodium hydroxide aqueous solution to 90° C., and then adding α,ω-dihydroxy polydimethylsiloxane for 3 hours to alkalize the α,ω-dihydroxy polydimethylsiloxane to increase the number of surface hydroxyl groups for standby use;
[0017] S3: dissolving the alkalized α,ω-dihydroxy polydimethylsiloxane in an ethanol solution, adding benzoyl peroxide and maleic anhydride under heating conditions of 60-80° C. and stirring for 3 hours to obtain a maleic anhydride-grafted α,ω-dihydroxy polydimethylsiloxane composite solution;
[0018] S4: adding graphene powder to the above composite solution and stirring it ultrasonically to obtain a maleic anhydride grafted modified graphene intermediate mixture.
[0019] Preferably, the silicone adhesive comprises the following raw materials in parts by weight: 85 parts of base adhesive, 15 parts of filler, 15 parts of plasticizer, 6 parts of cross-linking agent, 4 parts of coupling agent, 0.5 parts of catalyst, and 1 part of antibacterial and mildew-proof composite agent. The filler is a mixture of modified nano-calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:1.
[0020] The preparation method of the above antibacterial silicone adhesive comprises the following steps:
[0021] 1) According to the proportion, take 50% of the base glue, plasticizer, and 50% of the filler and add them to the mixer, and stir them under vacuum at 80-90°C for 15-20 minutes. Add the remaining 50% of the base glue and the remaining 50% of the filler to the mixer, and continue to stir under vacuum for 15-20 minutes;
[0022] 2) adding the antibacterial and antifungal compound and 50% of the coupling agent into a grinder, grinding at room temperature for 10-20 minutes, and then adding the ground materials into the mixer described in step 1);
[0023] 3) After the mixture is cooled to room temperature, a cross-linking agent, the remaining 50% coupling agent and a catalyst are added and mixed, and silicone glue is obtained by discharging the material.
[0024] Preferably, the vacuum degree of the stirrer in step 1) is 0.07-0.05 MPa, and the rotation speed is 600-800 rpm.
[0025] Preferably, the antibacterial and antifungal composite agent is composed of β-cyclodextrin, octyl isothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:2:1.
[0026] The beneficial effects of the present invention are:
[0027] 1. Nano calcium carbonate has a strong hydrophilicity and is easy to agglomerate due to its large specific surface area and the presence of more hydrophilic functional groups on the surface. When used as a silicone filler, it has a high moisture content and is difficult to remove. At the same time, it is difficult to disperse in the resin. The technical solution performs surface modification on nano calcium carbonate, which can effectively solve the problem that nano calcium carbonate is not easy to disperse as a filler.
[0028] 2. In the technical scheme, maleic anhydride is used to graft α, ω-dihydroxypolydimethylsiloxane, and then it is reacted with graphene oxide by ultrasonic stirring. Graphene oxide and maleic anhydride form a graphene oxide / maleic anhydride complex due to hydrogen bonding, and a maleic anhydride grafted α, ω-dihydroxypolydimethylsiloxane intermediate dispersion is obtained. The dispersion can fully achieve good blending with the base rubber. Graphene oxide is introduced into the base rubber by chemical modification. The acid and alkali resistance and corrosion resistance of the modified silicone rubber are significantly improved.
[0029] 3. In practical applications, silicone adhesives have high requirements for bonding and mechanical properties, and they are also required to have good rheological properties. For example, they should be easy to construct in various scenarios such as grooves, inclined or vertical surfaces, and should not flow during application, that is, they should have good thixotropy. When applying the adhesive manually or pneumatically, the adhesive should be discharged smoothly, that is, it should have good extrudability. The rheological properties can be effectively changed by adding modified nano-calcium carbonate and modified graphene.
[0030] 4. Existing antibacterial silicone glue can basically meet the antibacterial performance requirements, but the main problem is that the antibacterial durability is insufficient. The present invention mainly starts from improving the antibacterial durability of silicone glue, and by optimizing the raw material composition and preparation process, the durability of the antibacterial performance of silicone glue can be significantly improved. DETAILED DESCRIPTION
[0031] The present application is further described in detail below in combination with comparative examples and embodiments. It should be noted that, under the premise of no conflict, the embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0032] Firstly, modified calcium carbonate and maleic anhydride grafted modified graphene intermediate are prepared for use.
[0033] Preparation of modified nano calcium carbonate: At 70°C, 30% volume concentration of CO2 is introduced into the lime emulsion. After the carbonization reaction generates calcium carbonate, CH3(CH2) is first added. 10 COONa, the amount of which is 8% of the weight of calcium carbonate, is stirred for 50 minutes, and CaCl2 is continued to be added, the amount of which is 2% of the weight of calcium carbonate, and stirring is continued for 15 minutes. After aging for 35 minutes, filtering, and drying at 80°C, modified nano calcium carbonate is obtained.
[0034] Preparation of maleic anhydride grafted modified graphene intermediate:
[0035] S1: Take 10 parts of α,ω-dihydroxypolydimethylsiloxane, 12 parts of maleic anhydride, 3 parts of benzoyl peroxide, and 100 parts of graphene powder by weight; set aside.
[0036] S2: Heat a 15% mass concentration sodium hydroxide solution to 90°C, then add α,ω-dihydroxypolydimethylsiloxane to alkalize for 3 hours to increase the number of hydroxyl groups on the surface of the α,ω-dihydroxypolydimethylsiloxane for standby use, and the mass volume ratio (g / mL) of α,ω-dihydroxypolydimethylsiloxane to the sodium hydroxide solution is 1:3;
[0037] S3: According to the volume ratio of 1:5, the alkalized α,ω-dihydroxy polydimethylsiloxane is further dissolved in an ethanol solution with a mass fraction of 80%, and benzoyl peroxide and maleic anhydride are added under heating at 70°C and stirred for 3 hours to obtain a maleic anhydride grafted α,ω-dihydroxy polydimethylsiloxane composite solution;
[0038] S4: adding graphene powder to the above composite solution and stirring it ultrasonically to obtain a maleic anhydride grafted modified graphene intermediate.
[0039] Example 1
[0040] Take the raw materials according to the following ratio: 85 parts of α,ω-dihydroxy polydimethylsiloxane, 15 parts of a mixture of modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:1, 15 parts of polydimethylsiloxane, 6 parts of methyltriacetoxysilane, 4 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.5 parts of dibutyltin diacetate, and 1 part of a mixture of β-cyclodextrin, octyl isothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:2:1;
[0041] The steps for preparing the antibacterial silicone adhesive in this embodiment are as follows:
[0042] 1) According to the ratio, 50wt% α, ω-dihydroxy polydimethylsiloxane, polydimethylsiloxane, and 50wt% filler (a mixture of modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:1) are added to a blender, and the mixture is stirred in vacuum for 20 min at a temperature of 85°C, a vacuum degree of 0.01MPa, and a rotation speed of 800rpm. The remaining 50wt% α, ω-dihydroxy polydimethylsiloxane and the remaining 50wt% filler (a mixture of modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:1) are added to the blender, and the vacuum stirring is continued for 18min under the same conditions;
[0043] 2) adding an antibacterial and antifungal compound (a mixture of β-cyclodextrin, octyl isothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:2:1) and 50 wt % of a coupling agent (γ-(2,3-epoxypropoxy)propyltrimethoxysilane) into a grinder, grinding at room temperature for 15 min, and then adding the grinding mixture to the mixer described in step 1);
[0044] 3) After the mixture is cooled to room temperature, a crosslinking agent (methyltriacetoxysilane), the remaining 50 wt% coupling agent and a catalyst (dibutyltin diacetate) are added and mixed and stirred for 40 minutes to obtain silicone glue.
[0045] Example 2
[0046] Take the raw materials according to the following ratio: 90 parts of α,ω-dihydroxy polydimethylsiloxane, 20 parts of a mixture of modified nano-calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:2, 20 parts of polydimethylsiloxane, 5 parts of methyltriacetoxysilane, 3 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.8 parts of dibutyltin diacetate, and 2 parts of a mixture of β-cyclodextrin, octylisothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:1:1;
[0047] The steps for preparing the antibacterial silicone adhesive in this embodiment are as follows:
[0048] 1) According to the ratio, 50% α, ω-dihydroxy polydimethylsiloxane, polydimethylsiloxane, and 50% filler (a mixture of modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:2) are added to a blender, and the mixture is stirred in a vacuum at 85°C, 0.01 MPa, and 800 rpm for 20 min. The remaining 50% α, ω-dihydroxy polydimethylsiloxane and the remaining 50% filler (a mixture of modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:2) are added to the blender, and the vacuum stirring is continued for 18 min under the same conditions;
[0049] 2) adding an antibacterial and antifungal compound (a mixture of β-cyclodextrin, octyl isothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:2:1) and 50% of a coupling agent (γ-(2,3-epoxypropoxy)propyltrimethoxysilane) into a grinder, grinding at room temperature for 15 minutes, and then adding the grinding mixture to the mixer described in step 1);
[0050] 3) After the mixture is cooled to room temperature, a crosslinking agent (methyltriacetoxysilane), the remaining 50% coupling agent and a catalyst (dibutyltin diacetate) are added and mixed and stirred for 20 minutes to obtain silicone glue.
[0051] Example 3
[0052] Take the raw materials according to the following ratio: 80 parts of α,ω-dihydroxy polydimethylsiloxane, 10 parts of a mixture of modified nano-calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:1.5, 10 parts of polydimethylsiloxane, 7 parts of methyltriacetoxysilane, 3 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.3 parts of dibutyltin diacetate, and 2 parts of a mixture of β-cyclodextrin, octyl isothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:1.5:1;
[0053] The steps for preparing the antibacterial silicone adhesive in this embodiment are as follows:
[0054] 1) According to the ratio, 50% α, ω-dihydroxy polydimethylsiloxane, polydimethylsiloxane, and 50% filler (a mixture of modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:1.5) are added to a blender, and the mixture is stirred in a vacuum at a temperature of 90°C, a vacuum degree of -0.03 MPa, and a rotation speed of 600 rpm for 15 min. The remaining 50% α, ω-dihydroxy polydimethylsiloxane and the remaining 50% filler (a mixture of modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:1.5) are added to the blender, and the vacuum stirring is continued for 18 min under the same conditions;
[0055] 2) adding an antibacterial and antifungal compound (a mixture of β-cyclodextrin, octyl isothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:1.5:1) and 50% of a coupling agent (γ-(2,3-epoxypropoxy)propyltrimethoxysilane) into a grinder, grinding at room temperature for 20 minutes, and then adding the grinding mixture to the mixer described in step 1);
[0056] 3) After the mixture is cooled to room temperature, a crosslinking agent (methyltriacetoxysilane), the remaining 50% coupling agent and a catalyst (dibutyltin diacetate) are added and mixed and stirred for 30 minutes to obtain silicone glue.
[0057] Comparative Example 1
[0058] The difference from Example 1 is that the filler is nano calcium carbonate.
[0059] Comparative Example 2
[0060] The difference from Example 1 is that the filler is a mixture of nano-calcium carbonate and graphene oxide in a mass ratio of 1:1.
[0061] Comparative Example 3
[0062] The difference from Example 2 is that the antibacterial and antifungal composite agent is silver nitrate nanoparticles.
[0063] Comparative Example 4
[0064] The difference from Example 3 is that the preparation method is:
[0065] 1) According to the ratio, α,ω-dihydroxy polydimethylsiloxane, polydimethylsiloxane, filler (a mixture of modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:1.5), and antibacterial and antifungal compound (a mixture of β-cyclodextrin, octyl isothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:1.5:1) are added into a blender, and the mixture is stirred in vacuum at 90°C, a vacuum degree of -0.03MPa, and a rotation speed of 600rpm for 30min;
[0066] 2) After the mixture is cooled to room temperature, a crosslinking agent (methyltriacetoxysilane), a coupling agent (γ-(2,3-epoxypropoxy)propyltrimethoxysilane) and a catalyst (dibutyltin diacetate) are added and mixed and stirred for 30 minutes to obtain silicone glue.
[0067] The silicone sealants prepared in Examples 1-3 and Comparative Examples 1-4 were tested for basic properties according to GB-T14683-2003 "Silicone Building Sealant" standard. The results are shown in Table 1 below:
[0068] Table 1 Test results of basic properties of silicone adhesive
[0069]
[0070] It can be seen from Table 1 above that the basic performance of the silicone adhesive prepared by the technical solution of the present invention is very excellent. After the modification of the filler and the optimization of the preparation process, the extrusion and elastic recovery rate, the fixed elongation adhesion, the adhesion after UV radiation and the adhesion after cold drawing-hot pressing of the silicone adhesive can be significantly optimized, and the surface drying time is appropriate.
[0071] Further, the antibacterial effect evaluation test of the silicone glue prepared by Examples 1-3 and Comparative Examples 1-4 was tested by the film sticking method specified in GB / T 21866-2008 "Determination of antibacterial property and antibacterial effect of antibacterial coatings (paint films)", and the test strains were Escherichia coli (ATCC25922) and Staphylococcus aureus (ATCC6538); and the anti-mildew effect evaluation was tested according to the test method specified in GB / T1741-2007 "Determination of mildew resistance of paint films", and the strains were six mixed molds including Aspergillus niger (AS 3.4463), Aspergillus terreus (AS 3.3935), Penicillium variotii (AS 3.4253), Penicillium funiculum (AS 3.3875), Chaetomium globosum (AS3.4254), and Aureobasidium pullulans (AS 3.3984). In addition, the antibacterial and mildew-proof silicone adhesive sample prepared by the present invention was treated with reference to the water treatment conditions for evaluating the durability of building water pipes specified in the standard JC / T939-2004 "Antibacterial Performance of Antibacterial Plastic Pipes for Buildings" (immersing the sample in a distilled water bath at 50±2°C for 16 hours) to evaluate its water-resistant, antibacterial and mildew-proof effect; at the same time, the antibacterial and mildew-proof silicone adhesive sample prepared by the present invention was treated with reference to the ultraviolet light conditions of the method for evaluating the antibacterial durability of paint films in the standard GB / T 21866-2008 to evaluate its light-resistant, antibacterial and mildew-proof effect. The test results are recorded in Table 2.
[0072] Table 2 Antibacterial and antifungal test results
[0073]
[0074]
[0075] It can be seen from Table 2 that the silicone gel prepared by the technical solution of the present invention has excellent antibacterial and mildew resistance.
Claims
1. An antibacterial silicone adhesive, characterized in that: The silicone adhesive comprises the following raw materials in parts by weight: 80-90 parts of base adhesive, 10-20 parts of filler, 10-20 parts of plasticizer, 5-8 parts of crosslinking agent, 3-5 parts of coupling agent, 0.2-0.8 parts of catalyst, and 1-2 parts of antibacterial and mildewproof composite agent. The filler is a mixture of modified nano calcium carbonate and maleic anhydride grafted modified graphene intermediate.
2. The antibacterial silicone adhesive according to claim 1, characterized in that: The mass ratio of the modified nano-calcium carbonate and the maleic anhydride grafted modified graphene intermediate mixture is 1:1-2.
3. The antibacterial silicone adhesive according to claim 1, characterized in that: The antibacterial and anti-mildew composite agent is composed of beta-cyclodextrin, octyl isothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:1-2:
1.
4. The antibacterial silicone adhesive according to claim 1, characterized in that: The base glue is α,ω-dihydroxy polydimethylsiloxane, the plasticizer is polydimethylsiloxane, the crosslinking agent is methyl triacetoxysilane, the coupling agent is γ-(2,3-epoxypropoxy)propyl trimethoxysilane, and the catalyst is dibutyltin diacetate.
5. The antibacterial silicone adhesive according to claim 1, characterized in that: The modified nano calcium carbonate preparation method is as follows: at 60-80°C, 20-40% CO2 is introduced into lime emulsion, and after the carbonization reaction is completed to generate calcium carbonate, CH3 (CH2) is first added. 10 COONa, the amount of which is 5-10% of the weight of calcium carbonate, is stirred for 50-60 minutes, and CaCl2 is continuously added, the amount of which is 0.5-2.5% of the weight of calcium carbonate, and the stirring is continued for 10-20 minutes. After aging for 30-40 minutes, the mixture is filtered and dried at 60-90°C to obtain modified nano calcium carbonate.
6. The antibacterial silicone adhesive according to claim 1, characterized in that: The preparation method of the maleic anhydride grafted modified graphene intermediate mixture is as follows: S1: By weight, take 10 parts of α,ω-dihydroxypolydimethylsiloxane, 12 parts of maleic anhydride, 3 parts of benzoyl peroxide, and 100 parts of graphene powder. S2: heating a 10-20% mass concentration sodium hydroxide aqueous solution to 90° C., and then adding α,ω-dihydroxy polydimethylsiloxane for 3 hours to alkalize the α,ω-dihydroxy polydimethylsiloxane to increase the number of surface hydroxyl groups for standby use; S3: dissolving the alkalized α,ω-dihydroxy polydimethylsiloxane in an ethanol solution, adding benzoyl peroxide and maleic anhydride under heating conditions of 60-80° C. and stirring for 3 hours to obtain a maleic anhydride-grafted α,ω-dihydroxy polydimethylsiloxane composite solution; S4: adding graphene powder to the above composite solution and stirring it ultrasonically to obtain a maleic anhydride grafted modified graphene intermediate mixture.
7. The antibacterial silicone adhesive according to claim 1, characterized in that: The silicone adhesive comprises the following raw materials in parts by weight: 85 parts of base adhesive, 15 parts of filler, 15 parts of plasticizer, 6 parts of cross-linking agent, 4 parts of coupling agent, 0.5 parts of catalyst, and 1 part of antibacterial and mildew-proof composite agent. The filler is a mixture of modified nano-calcium carbonate and maleic anhydride grafted modified graphene intermediate in a mass ratio of 1:
1.
8. A method for preparing an antibacterial silicone adhesive, characterized in that: Here are the steps: 1) According to the proportion, take 50% of the base glue, plasticizer, and 50% of the filler and add them to the mixer, and stir them under vacuum at 80-90°C for 15-20 minutes. Add the remaining 50% of the base glue and the remaining 50% of the filler to the mixer, and continue to stir under vacuum for 15-20 minutes; 2) adding the antibacterial and antifungal compound and 50% of the coupling agent into a grinder, grinding at room temperature for 10-20 minutes, and then adding the ground materials into the mixer described in step 1); 3) After the mixture is cooled to room temperature, a cross-linking agent, the remaining 50% coupling agent and a catalyst are added and mixed and stirred for 20-50 minutes to obtain silicone rubber.
9. The method for preparing an antibacterial silicone adhesive according to claim 8, characterized in that: Step 1) The vacuum degree of the stirrer is -0.07-0.05MPa, and the rotation speed is 600-800rpm.
10. The method for preparing an antibacterial silicone adhesive according to claim 8, characterized in that: The antibacterial and anti-mildew composite agent is composed of beta-cyclodextrin, octyl isothiazolinone and tetragonal zinc oxide whiskers in a mass ratio of 1:2:1.
Citation Information
Patent Citations
Long-acting antibacterial and mildew-proof silicone adhesive and preparation method thereof
CN103773308A
Silicone adhesive with mildew-proof effect
CN113881393A
High-temperature-resistant mildew-preventive silicone sealant and method for preparing same
CN109575872A
Silicone adhesive with antibacterial and mildew-proof effects and preparation method thereof
CN112239645A
Silicone adhesive as well as preparation method and application thereof
CN116179148A
Cited By
Mildew-proof flame-retardant silicone sealant for buildings and preparation method thereof
CN121950248A